Hypofractionated irradiation in 794 elderly breast cancer patients: An observational study. Issue 2 (25th August 2019) - La Rocca, Eliana; Meneghini, Elisabetta; Dispinzieri, Michela; Fiorentino, Alba; Bonfantini, Francesca; Di Cosimo, Serena; Gennaro, Massimiliano; Cosentino, Vito; Sant, Milena; Pignoli, Emanuele; Valdagni, Riccardo; Lozza, Laura; et al.
Abstract: To assess the efficacy, and the acute and late toxicity of hypofractionated radiotherapy (Hypo‐RT), and the impact of age and comorbidities on disease progression and death in elderly breast cancer (BC) patients. Women aged ≥65 years who received Hypo‐RT (42.4 Gy in 16 fractions, plus a boost for high‐risk patients) were considered for the present analysis. Competing risk analysis was used to estimate the 5‐year cumulative incidence of BC progression and BC‐related death, calculating the adjusted subhazard ratios (SHR) with 95% confidence intervals (95%CI) in relation to age, hypertension‐augmented Charlson Comorbidity Index (hCCI), tumor characteristics, and chemotherapy. The sample included 794 patients with a median age of 74 years (range 65‐91 years). At the baseline, 70% of these patients had at least one comorbidity. With a median follow‐up of 48.3 months, the 5‐year cumulative incidence of BC progression and BC‐related death was 6.7% (95%CI 4.8%‐9.2%) and 2.3% (95%CI 1.2%‐3.9%), respectively. Old age (≥80 years) and a high burden of comorbidity (hCCI ≥ 2) were independently associated with BC progression. Hypo‐RT is safe in elderly BC patients, but age and comorbidities influence BC progression. Further studies are warranted.